Impact of muscle volume loss on acute oral mucositis in patients undergoing concurrent chemoradiotherapy after oral cancer resection. Issue 9 (September 2021) - Yamaguchi, T.; Makiguchi, T.; Nakamura, H.; Yamatsu, Y.; Hirai, Y.; Shoda, K.; Suzuki, K.; Kim, M.; Kurozumi, S.; Motegi, S.I.; Shirabe, K.; Yokoo, S.
Abstract: This study evaluated the association between skeletal muscle mass depletion and severe oral mucositis in patients undergoing concurrent chemoradiotherapy after oral cancer resection. Skeletal muscle mass was evaluated in 60 patients using the skeletal muscle index, which was based on skeletal muscle cross-sectional area (on computed tomography) at the level of the third lumbar vertebra. In accordance with the grading criteria of the Radiation Therapy Oncology Group, patients with a grade ≥3 were defined as having severe oral mucositis. Multivariate logistic regression analysis was used to evaluate independent risk factors for severe oral mucositis. Eleven patients (18.3%) were diagnosed with low skeletal muscle mass. Severe oral mucositis occurred in 17 (28.3%) patients, and the mean skeletal muscle index was 42.8 cm 2 /m 2 . A low skeletal muscle mass (hazard ratio 18.1; P = 0.001) and a chemotherapy regimen consisting of 5-fluorouracil and cisplatin (versus cisplatin only) (hazard ratio 5.5; P = 0.015) were independent risk factors for severe oral mucositis. Future prospective studies are warranted to identify effective pre- and perioperative exercises and nutrition programmes to increase low skeletal muscle mass and reduce the incidence of severe oral mucositis in patients undergoing concurrent chemoradiotherapy after oral cancer resection.